Effect of Hydroxycut Intake on Fasted and Postprandial Lipemia in Rats - Daher, Costantine F. (2015)
Hydroxycut, an herbal supplement not currently defined as a drug, is frequently sold over the counter to increase exercise performance, build muscles, and burn fat. The effects of 8 wk of hydroxycut-induced changes on blood lipid profile in rats fed with either regular or high-fat diet were evaluated. Regardless of fat content in the diet, the doses of hydroxycut used significantly decreased fasting serum concentrations of cholesterol, triacylglycerol (TAG), low-density lipoprotein (LDL) cholesterol, total apolipoprotein B (apo B), and LDL/high-density lipoprotein (HDL) cholesterol ratio. A significant increase in serum blood glucose level was observed with hydroxycut intake in the presence of a high-fat diet. No hydroxycut-related changes in serum activities of serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate dehydrogenase (SGPT), lactate dehydrogenase (LDH), and creatinine phosphokinase (CPK) enzymes were noted, indicating no liver damage occurred. A decrease in liver fat content was observed with hydroxycut intake. The drug did not affect the number and composition of secreted very-low-density lipoprotein (VLDL) particles except for a decrease in VLDL TAG when the fat content in the diet was high. Hydroxycut reduced significantly LDL apo B and LDL TAG and cholesterol concentrations. Hydroxycut increased TAG and cholesterol excretion in feces. A single intragastric food load containing hydroxycut reduced significantly postprandial plasma TAG concentration in a dose-dependent manner. In conclusion, hydroxycut intake in recommended doses exerts a beneficial impact on atherosclerosis, an effect attributed to improved clearance and metabolism of lipoprotein particles, and to a lesser extent to an increased excretion of TAG and cholesterol in the feces. More studies are needed to ensure the safety of long-term use of hydroxycut.